2012
DOI: 10.1523/jneurosci.5633-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Cell-Intrinsic Role for Serum Response Factor in Glial Specification in the CNS

Abstract: Astrocytes and oligodendrocytes play crucial roles in nearly every facet of nervous system development and function, including neuronal migration, synaptogenesis, synaptic plasticity, and myelination. Previous studies have widely characterized the signaling pathways important for astrocyte differentiation and unveiled a number of transcription factors that guide oligodendrocyte differentiation in the CNS. However, the identities of the transcription factors critical for astrocyte specification in the brain rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 78 publications
1
17
0
Order By: Relevance
“…Thus, the present study indicates that overexpression of SRF promotes oligodendrocyte maturation. Since the original submission of our study, Lu and Ramanan have shown that knockout of Srf in nestin expressing neural progenitor cells causes a 50% reduction of OPCs in postnatal mice (Lu and Ramanan, 2012). Our data corroborate and add to their observation by showing that SRF is likely involved in the transition from early stage progenitor to mature OL, given that we observed the strongest colocalization of SRF with CNPase in vivo ; during maturation of OLs, CNPase expression is apparent during the transition from OPC to mature OL, followed by MBP and APC expression, with some temporal overlap evident (Scherer et al, 1994, Wada et al, 2000, See et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the present study indicates that overexpression of SRF promotes oligodendrocyte maturation. Since the original submission of our study, Lu and Ramanan have shown that knockout of Srf in nestin expressing neural progenitor cells causes a 50% reduction of OPCs in postnatal mice (Lu and Ramanan, 2012). Our data corroborate and add to their observation by showing that SRF is likely involved in the transition from early stage progenitor to mature OL, given that we observed the strongest colocalization of SRF with CNPase in vivo ; during maturation of OLs, CNPase expression is apparent during the transition from OPC to mature OL, followed by MBP and APC expression, with some temporal overlap evident (Scherer et al, 1994, Wada et al, 2000, See et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…During this time, numerous secreted signals -notably Sonic hedgehog (Shh), fibroblast growth factors (FGFs), Wnts, Notch/Delta, bone morphogenetic proteins (BMPs) and cytokinesact together to control cell fate spatially and temporally, leading to the presence of specific domains that selectively generate either astrocytes or OPCs (Rowitch and Kriegstein, 2010;Zuchero and Barres, 2013). Key transcription factors involved at this time include Sox9, nuclear factor I and serum response factor for general gliogenesis, and Olig1/Olig2 for OPC production (Rowitch and Kriegstein, 2010;Lu and Ramanan, 2012). Interestingly, astrocytes generated in distinct regions have important functional differences that are just beginning to be revealed (reviewed by Molofsky and Deneen, 2015).…”
Section: Origins and Specification Of Gliamentioning
confidence: 99%
“…SRF has distinct roles in glial cells and neurons. SRF is implicated in glial specification (Lu & Ramanan, 2012) and SRF in astrocytes may modulate ocular dominance plasticity (Paul et al, 2010). In neurons, SRF is not essential for survival but is critical for induction and maintenance of LTP (Ramanan et al, 2005) and maintenance of LTD (Etkin et al, 2006;Smith-Hicks et al, 2010).…”
Section: A Critical Role For Srf In Circuit Rewiring and Plasticitymentioning
confidence: 99%